Heating of an annular plate under the effects of thermal buffer with phase change material in a trapezoidal vented cavity under convection of hot liquid with magnetic field - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Elsevier France-Editions Scientifiques Medicales Elsevier, 2026)
Heating of an annular plate (AN-PL) in a ventilated trapezoidal enclosure is studied under magnetic field effects. A thermal buffer is obtained in the inner part of the AN-PL by using phase change material (PCM). Finite element based simulation of the coupled system is performed while impacts of flow Reynolds number (Re), inlet temperature of hot liquid and magnetic field parameters on the temperature rise of the plate, and melting time (tf) are explored. The time at which the PCM's effect on AN-PL temperature enhancement becomes effective is indicated by the critical time (tc). The values of tc and tf drop by around 37.8% and 33.3% at the maximum Re. At the lowest Re case, PCM results in an AN-PL temperature increase of 3.1 degrees C in comparison to the case without PCM. Magnetic field parameters are effective in the flow distributions near the inlet port, but they have a very small effect on the heating of AN-PL. In contrast to the reference scenario without PCM and the lowest inlet temperature, PCM produces the largest heating of the AN-PL at the highest Re and inlet temperature, resulting in a higher plate temperature of 21.2 degrees C. When AN-PL is exposed to forced convection of hot liquid in a ventilated enclosure, PCM is shown to be a very effective passive thermal management technique. A variety of industrial applications, such as material processing, process heating, drying applications, and heat exchangers, may utilize the results.
Keywords: Annular plate; PCM; Heating application; Magnetic field; Finite element method